Tafsir Modern Di Indonesia Abad ke-21: Identifikasi Karakteristik Produk Tafsir Pada Tahun 2001-2022 - Dwi Nur Aisa, Latifah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2024)
This study examines the development of modern Qur’anic exegesis in Indonesia from the early 21st century to 2022, focusing on five representative works: Tafsir al-Misbah, Tafsir Inspirasi, Tafsir Qur’an per Kata, Pesan-pesan Al-Qur’an, and Tafsir Ringkas Al-Qur’an Al-Karim. A qualitative-descriptive approach, drawing on the theoretical frameworks of Mun’im Sirry and Johanna Pink, was employed to identify characteristics of modern exegesis. The findings indicate that most modern Indonesian exegetical works emphasize guidance, adopt systematic writing techniques (such as footnotes), and respond to the evolving social context. However, not all of them explicitly manifest the “inner-logic” of the Qur’an as advocated by Pink or engage comprehensively with local culture in the manner suggested by Sirry. Further, various exegetical styles emerge: from thematic discussions featuring poetry (Djohan Effendi), word-by-word elaboration (Ahmad Hatta), to the integration of contemporary hermeneutics (Quraish Shihab). This study concludes that modern Qur’anic exegesis in Indonesia is diverse and continues to evolve, reflecting a reformist spirit firmly rooted in its traditional heritage. Future research should explore a broader range of exegetical works and assess their effectiveness in addressing the challenges faced by contemporary Muslim communities.